2013
DOI: 10.1155/2013/859763
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparesis after Operation of Astrocytoma Grade II in Adults: Effects of Acupuncture on Sensory-Motor Behavior and Quality of Life

Abstract: To evaluate the effect of acupuncture on hemiparesis and quality of life for adults with brain astrocytoma grade II, we conducted a randomized, observer-blinded clinical trial. Fifty-eight patients were randomized to standard rehabilitation (SR) therapy without acupuncture (n = 20), SR plus standard acupuncture (SA) (n = 19), and SR plus individualized acupuncture (IA) (n = 19). SA points were PC6, SP6, HT1, LU5, BL40, and ST36, while a special concept called “connecting and regulation Ren and Du” and “Jin-3-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Brain tumor patients desire interventions that will help them redefine hope and improve their HRQoL . The current review was only able to identify two RCTs where the intervention group showed significant improvement in HRQoL over the control group(s)—a home‐based psychosocial intervention and individualized acupuncture combined with standard rehabilitation . Yet efforts are underway to further explore acupuncture and psychosocial interventions with respect to effects on HRQoL in these patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Brain tumor patients desire interventions that will help them redefine hope and improve their HRQoL . The current review was only able to identify two RCTs where the intervention group showed significant improvement in HRQoL over the control group(s)—a home‐based psychosocial intervention and individualized acupuncture combined with standard rehabilitation . Yet efforts are underway to further explore acupuncture and psychosocial interventions with respect to effects on HRQoL in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the effect of Boswellia serrata (BS, extract of Indian frankincense) on cerebral edema. Finally, a single study examined the effect of acupuncture (individualized or standardized) combined with standard rehabilitation, versus standard rehabilitation alone (standard of care), on hemiparesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations